Engineering Geometric Asymmetry for Dynamic Susceptibility Control in Nanorings - Saavedra-Díaz, E (IOP Publishing Ltd, 2025)
We present a micromagnetic simulation study on asymmetric magnetic nanorings, focusing on the control of dynamic susceptibility through geometric design. When truncated geometrically of Permalloy nanorings while keeping the central axis fixed, we introduce planar asymmetry and examine its effect on the equilibrium magnetization states and spin-wave dynamics. The simulations show a clear transition from transversal to vortex-like configurations as the geometry becomes increasingly asymmetric. This variation alters the system s energy landscape and changes the spatial characteristics of the resonant modes. In cases with partial asymmetry, we observe complex excitation patterns that become more localized as the geometry approaches symmetry. The analysis of dynamic susceptibility and spatial Fourier spectra confirms that planar asymmetry can be used to tailor the magnetic response. These results provide a basis for designing nanostructures with tunable dynamical properties for potential applications in magnonics and spintronics.